Development of test method for anti-amoebic activity - Nurulhazwani, Bt Mohd Rafiee (Universiti Malaysia Sarawak (UNIMAS), 2012)
A study was carried out to develop a preliminary method of antiamoebic screening test. Collection water samples were conducted in less polluted pond at Sarawak Golf Club UNIMAS to isolate nonpathogenic amoeba. Stepwise optimisation to initial amoeba isolation protocol resulted in a protocol which was applied successful to isolate and culture amoeba. The antiamoebic activity was conducted by treating free living amoebas with 50 ~g/ml concentration of Amino acid-Thiourea derivative. The viability of cells was compared with the treatment Thiourea control and NaCl cytotoxicity control with the same concentration. The antiamoebic activity was based on comparison of percentage of viable cells from 50 first views of counted cells under 100x magnification inverted microscope. Data was analysed using one-way ANOV A and significant data was analysed with Fisher's LSD test. Results of treatment showed toxicity of Amino acid-thiourea derivative on free living amoeba compared to NaCI was successfully developed. The prototype of the model antiamoebic activity screening test was established preliminary method for further detail study. The study suggests that antiamoebic activity of this compound may further be explored in the future by using higher concentration ofcompound.